Delivery Performance Improvement Using Six Sigma Method: A Case Study at FMC Agricultural Manufacturing - Satyana Primandaru; Soeparno (Institut Teknologi Sepuluh Nopember, 2019)
PT. FMC is a manufacturing company to produce pesticides in 3classifications: herbicides, fungicides and insecticides. The use ofpesticides is very important to maintain the quality of the crop. Delivery isan important metric because delivery has big influence to customersatisfaction. The delivery of products may not be late because it willdisrupt the consumer production chain. However, PT. FMC deliveryperformance faces a big issue. This research focuses on how companiesare able to identify problems, analyze and solve these problems using theSix Sigma methodology. This method is used because the Six Sigmamethodology has a cycle of how companies solve a problem that candisrupt business processes. The research found that problems in thebusiness process are categorized into 3 causes, namely (1) delays in thearrival of material both raw material and packaging material; (2) thecustomer delays delivery several times; and (3) the Warehouse Leader islate in inputting data and Post Goods Issue.